Examining how country-level science policy shapes publication patterns: The case of Poland - Korytkowski, Przemysław; Kulczycki, Emanuel (My University, 2019)
This country case study describes how science policy instruments are designed to shape publication patterns and identifies the changes in researchers’ productivity that can be observed over the period 2009–2016 in Poland by analysing data on 452,277 publications submitted to the country’s national research evaluation system. Our analysis reveals that policy instruments used in the country’s national research evaluation system, academic promotion procedures and competitive grants have increased the number of articles with an impact factor without compromising publication quality, as measured by a bibliometric indicator. Our findings highlight that only clear and stable incentives have influenced researchers’ publications. Therefore, patterns in scholarly book publications—for which regulations were not clear and stable—have not been significantly shaped by science policy.
This work was supported by the DIALOG Programme [Grant name ‘Research into Excellence Patterns in Science and Art’].
Keywords: Science policy; Incentives; Poland; Research evaluation; Publication patterns